CONCEPTUAL FOUNDATIONS OF PROFESSIONAL ORIENTATION AND CAREER COUNSELING FOR STUDENTS OF PROFESSIONAL PRE-HIGHER EDUCATION (Innovative professional education, 2025)
The conceptual foundations of vocational guidance and career counseling for students of professional higher education based on psychological, pedagogical and career development theories are considered. They help students make an informed choice of profession, align students’ skills, interests, and values with the requirements of the labor market, ensuring a successful career transition. It highlights the use of assessment tools, digital technologies, internships, and mentoring programs that enhance students’ ability to make informed career decisions, develop necessary skills, and make a smooth transition to the workforce
Keywords: professional higher education, conceptual framework, professional orientation, career counseling, students of professional higher education